Herramientas basadas en IA para la educación y comunicación en niños con TEA - Espinoza Mazzini, Karla Dessire (2025)
AI-based tools are transforming the education of children with ASD, providing accessible and scalable solutions for their educational and communication needs. This research was based on a systematic review where the PRISMA method was used to identify best alternatives and outstanding practices of the last five years to identify their benefits and limitations. In addition, the AHP-TOPSIS multi-criteria approach was implemented to compare tools such as humanoid robots, mobile applications and immersive extended reality environments, considering different criteria such as costs, accessibility, adaptability and security to carry out an evaluation and selection of the best alternative. Tools such as QTrobot and Metaverse were highlighted for their ability to improve communication and social skills, on the other hand, options such as MOLHEM and Aawn stand out for being accessible in contexts with limited resources. However, challenges were identified such as high implementation costs and dependence on advanced infrastructures in some solutions. This research not only shows the positive impact of AI-based tools in the educational context of children with ASD, but also identifies the best alternatives that prioritize inclusion and accessibility, thereby contributing to educational environments with accessible solutions adapted to their needs. the needs of children with ASD so that they can reach their full potential.